PENGALAMAN CALON GURU SAINS DALAM PEMBELAJARAN DARING SELAMA MASA PANDEMI COVID-19 - Nur Eka Kusuma Hindrasti; Ardi Widhia Sabekti (Pendidikan Kimia Unimus, 2020)
This study aims to determine the experience of preservice science teacher in online learning during the Covid-19 pandemic in Tanjungpinang. This research is a survey research, with a quantitative descriptive research method. The sample is determined using total sampling technique, with totaling 278 peoples. The research instrument used a questionnaire in the Google Form. The results showed that almost all preservice science teacher took part in online learning from home using smartphone devices and learning platforms in the form of whatsapp and google classroom, as well as video conferencing, namely zoom. Most preservice science teacher still do practicums that are carried out independently at home and also virtually. Limited networks and internet data packages are two major aspects that interfere with online learning. However, preservice science teacher feel the benefits of online learning, among others, being efficient in terms of time, increasing digital technology literacy, and avoiding Covid-19.